Infrastructure as a strategy for land conservation Kongjian Yu’s work - Olórtegui, Ingrid (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5180 This article will explain the strategies used by Chinese architect Kongjian Yu and his Turenscape team for analyzing and understanding the land as a starting point for the development of his landscape proposals, which challenge the trend of massive use of concrete in China. Returning to the roots of culture, nature and understanding of the land to propose projects that organically manage the variability of nature, especially in its relationship with water, will be related to the incipient development of natural infrastructure in the Peruvian context. Yu’s experience manages to link the so-called ecological infrastructure with urban development, whose simile in Peru would be natural infrastructure, which is conceived as the development of natural space associated with the origin of water sources in rural areas, while the implementation of gray infrastructure still prevails in the cities.